PHYLOGENETIC RELATIONSHIPS WITHIN FAMILIES MYRTACEAE IN TRIPA PEAT SWAMP FOREST USING INTERNAL TRANSCRIBED SPACER (ITS) - Ardhana Yulisma; Zairin Thomy; Essy Harnelly (Universitas Syiah Kuala, 2018)
The Tripa peat swamp forest is located on the west coast of Aceh province and falls administratively under the two districts of Nagan Raya and Aceh Barat Daya. Tripa peat swamp forest has a high diversity of plants. The previous research discovered that Myrtaceae is one of the dominant families in the forest. This study aimed to predict phylogenetic relationships among trees species within families Myrtaceae that live in the Tripa peat swamp forest using Internal Transcribed Spacer (ITS). The research was conducted at Laboratory of Forest Genetics and Molecular Forestry, Faculty of Forestry, IPB from June 2015 to December 2016. The methods were conducted with an experimental laboratory of molecular identification consisting of DNA extraction, amplification, and sequencing. Data was analyze using BioEdit, Clustal X, Mega 6, and BLAST. The morphology identification reported that there were four trees species within families Myrtaceae, i.e., Syzygium sp 1, Syzygium garciniifolium, Syzygium leptostemon and Tristaniopsis whiteana. Reconstruction of phylogenetic tree using the Neighbor-Joining (NJ) method 1000x showed that the ITS region was successfully to predict phylogenetic relationships within genus Syzygium and Tristaniopsis.Keywords: tripa peat swamp forest, tree species, phylogenetic, myrtaceae, internal transcribed spacer